CCR2-dependent monocyte-derived macrophages resolve inflammation and restore gut motility in postoperative ileus. Issue 12 (14th June 2017) - Farro, Giovanna; Stakenborg, Michelle; Gomez-Pinilla, Pedro J; Labeeuw, Evelien; Goverse, Gera; Giovangiulio, Martina Di; Stakenborg, Nathalie; Meroni, Elisa; D'Errico, Francesca; Elkrim, Yvon; Laoui, Damya; Lisowski, Zofia M; et al.
Abstract : Objective: Postoperative ileus (POI) is assumed to result from myeloid cells infiltrating the intestinal muscularis externa (ME) in patients undergoing abdominal surgery. In the current study, we investigated the role of infiltrating monocytes in a murine model of intestinal manipulation (IM)-induced POI in order to clarify whether monocytes mediate tissue damage and intestinal dysfunction or they are rather involved in the recovery of gastrointestinal (GI) motility. Design: IM was performed in mice with defective monocyte migration to tissues (C-C motif chemokine receptor 2, Ccr2 −/ − mice) and wild-type (WT) mice to study the role of monocytes and monocyte-derived macrophages (MΦs) during onset and resolution of ME inflammation. Results: At early time points, IM-induced GI transit delay and inflammation were equal in WT and Ccr2 − / − mice. However, GI transit recovery after IM was significantly delayed in Ccr2 − / − mice compared with WT mice, associated with increased neutrophil-mediated immunopathology and persistent impaired neuromuscular function. During recovery, monocyte-derived MΦs acquire pro-resolving features that aided in the resolution of inflammation. In line, bone marrow reconstitution and treatment with MΦ colony-stimulating factor 1 enhanced monocyte recruitment and MΦ differentiation and ameliorated GI transit in Ccr2 − / − mice. Conclusion: Our study reveals a critical role for monocyte-derived MΦs in restoring intestinal homeostasis after surgical trauma. From a therapeutic point of view, our data indicate that inappropriate targeting of monocytes may increase neutrophil-mediated immunopathology and prolong the clinical outcome of POI, while future therapies should be aimed at enhancing MΦ physiological repair functions.